Formal and informal systems in prison - Macanović Nebojša (Temida, 2007)
Main question of modern penological theory and penitentiary practise is finding deeper social sense through general goal, which we define as resocialization of prisoners and creating conditions for successful life after leaving prison. Success of resocialization depends also on attitude of prisoners to formal system and following the rules and principles of that system. Opposite to formal system which is based on prison staff and normative system (Law of carrying out of a sentence and Book of regulations for house rules), exists informal system which is based on prisoners and their mutual relationships, as well as on prisoner's codex, and which has negative influence to resocilazation process. Attitude of prisoners to formal system during serving a sentence represents very significant indicator of prisoner's readiness for return to community and acceptance of society norms.